2018
DOI: 10.3390/microorganisms6030074
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Characterizing Escherichia coli from Cattle Feces: A Cautionary Tale

Abstract: Shiga toxin-producing Escherichia coli (STEC) are diverse bacteria, with seven serogroups (O26, O45, O103, O111, O121, O145, O157; “Top 7”) of interest due to their predominance in human disease. Confirmation of STEC relies on a combination of culturing, immunological and molecular assays, but no single gold standard for identification exists. In this study, we compared analysis of STEC between three independent laboratories (LAB) using different methodologies. In LAB A, colonies of Top 7 were picked after ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A significant finding of the present study was that intermittent false stx positives could in twenty-two cases be possibly related to presence of fragments of stx-encoding phages (Table 2), especially as genomes of the majority of strains possessed multiple fragments of identifiable stx-encoding phages (Table 3). The Conrad et al [10] primers used at initial isolation have had positive amplification of stx even with one or two base-pair mismatches [33], but the possible intermittent binding of primers to stx fragments has not been previously reported, likely as only a subset of stx fragments may have influenced PCR results. Larger fragments with highest stx sequence integrity would be the most likely to intermittently bind to PCR primers, although it was not possible in the present study to verify which if any of the stx fragments led to false-positive PCRs.…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…A significant finding of the present study was that intermittent false stx positives could in twenty-two cases be possibly related to presence of fragments of stx-encoding phages (Table 2), especially as genomes of the majority of strains possessed multiple fragments of identifiable stx-encoding phages (Table 3). The Conrad et al [10] primers used at initial isolation have had positive amplification of stx even with one or two base-pair mismatches [33], but the possible intermittent binding of primers to stx fragments has not been previously reported, likely as only a subset of stx fragments may have influenced PCR results. Larger fragments with highest stx sequence integrity would be the most likely to intermittently bind to PCR primers, although it was not possible in the present study to verify which if any of the stx fragments led to false-positive PCRs.…”
Section: Plos Onementioning
confidence: 98%
“…In summary, generic E. coli strains showed false positive amplification for serogroups: O26 (n = 6), O45 (n = 2), O103 (n = 6), O145 (n = 2), and O157 (n = 5). The exceptions were O121 which had stable serogroup detection (Table 4) and O111 which was not included in this study due to previously noted stable serogroup and stx 1 detection [33].…”
Section: Serogroup and Serotypementioning
confidence: 99%
See 1 more Smart Citation
“…Similar results of O26 serogroup have been reported from Malaysia (25%), Asia-Pacific (7.2%) ( 40 ), Europe (3.5%) ( 41 ), Africa (7%) ( 42 ) and America (17%), ( 43 ) which are in agreement with our findings. However, a higher frequency of O26 serotype was observed in Iran (43.75%) ( 44 ), Malaysia (18.4%) ( 12 ) and Canada (62.6%) ( 45 ). Epidemiological surveillance indicates that the persistence of non-O157 serotypes, E. coli O26 is the one of the major serotypes of concern.…”
Section: Discussionmentioning
confidence: 94%
“…The HUS-associated STEC list and their non-motile derivatives were therefore expanded in Table 1A . These are the seven STEC priority serotypes most often associated with HC and HUS infections and sporadic cases worldwide ( Stanford et al., 2018 ); USDA study on the classification of non-O157 STEC from meat products are reported in Table 1B .…”
Section: Emerging Stec Serotypesmentioning
confidence: 99%